Methodology of using mobile Internet devices in the process of biology school course studying - Alla V. Stepanyuk; Liudmyla P. Mironets; Tetiana M. Olendr; Ivan M. Tsidylo; Oksana B. Stoliar (Academy of Cognitive and Natural Sciences, 2020)
This paper considers the problem of using mobile Internet devices in the process of biology studying in secondary schools. It has been examined how well the scientific problem is developed in pedagogical theory and educational practice. The methodology of using mobile Internet devices in the process of biology studying in a basic school, which involves the use of the Play Market server applications, Smart technologies and a website, has been created. After the analyses of the Play Market server content, there have been found several free of charge applications, which can be used while studying biology in a basic school. Among them are the following: Anatomy 4D, Animal 4D+, Augmented Reality Dinosaurs - my ARgalaxy, BioInc - Biomedical Plague, Plan+Net. Their choice is caused by the specifics of the object of biological cognition (life in all its manifestations) and the concept of bio(eco)centrism, which recognizes the life of any living system as the highest value. The paper suggests the original approach for homework checking, which involves besides computer control of students' learning outcomes, the use of Miracast wireless technology. This demands the owning of a smartphone, a multimedia projector, and a Google Chromecast type adapter. The methodology of conducting a mobile front-line survey at the lesson on the learned or current material in biology in the test form, with the help of the free Plickers application, has been presented. The expediency of using the website builder Ucoz.ua for creation of a training website in biology has been substantiated. The methodology of organizing the educational process in biology in a basic school using the training website has been developed. Recommendations for using a biology training website have been summarized. According to the results of the forming experiment, the effectiveness of the proposed methodology of using mobile Internet devices in the process of biology studying in a basic school has been substantiated.